2013
DOI: 10.1111/jfb.12065
|View full text |Cite
|
Sign up to set email alerts
|

Can sea trout Salmotrutta compromise successful eradication of Gyrodactylus salaris by hiding from CFT Legumin (rotenone) treatments?

Abstract: In this study, 34 anadromous brown trout (sea trout) Salmo trutta were equipped with acoustic transmitters in order to examine whether they performed avoidance behaviour in response to a CFT Legumin (rotenone) treatment in the Norwegian River Vefsna. Migratory behaviour of the S. trutta was monitored by use of 15 automatic listening stations and manual tracking in the lower part of the river, in the estuary and in the fjord. None of the studied S. trutta survived the rotenone treatment and no indications of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
(10 reference statements)
1
4
0
Order By: Relevance
“…They found no avoidance behaviour and no survival, which indicate a successful rotenone treatment. Similar to the findings of Davidsen et al [26], there were no avoidance behaviour in the Atlantic salmon and anadromous brown trout tagged in the study presented here, but in contrast no mortality was recorded which is an advantage of the Al treatment method. In another study, Mitamura et al [27] used a tag based on the design presented here to measure salinity during seaward migration of Atlantic salmon in a fjord in Norway.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…They found no avoidance behaviour and no survival, which indicate a successful rotenone treatment. Similar to the findings of Davidsen et al [26], there were no avoidance behaviour in the Atlantic salmon and anadromous brown trout tagged in the study presented here, but in contrast no mortality was recorded which is an advantage of the Al treatment method. In another study, Mitamura et al [27] used a tag based on the design presented here to measure salinity during seaward migration of Atlantic salmon in a fjord in Norway.…”
Section: Discussionsupporting
confidence: 92%
“…1) requirements. This demonstrates the flexibility and capacity provided by contemporary digital electronic fish tags to carry out on-board processing and analysis of sensor signals prior to transmission over the severely bandwidth-limited acoustic channel, a concept that has been utilized successfully in several subsequent telemetry studies [17,[25][26][27]. Even if the recorded sensor data must undergo substantial compression and loss of detail before acoustic transmission, the approach features an advantage over archival tags in that no recapture of the tag is needed to recover the data [25].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…During the marine feeding migration from September to March, most of the brown trout stayed in brackish water (5–25‰) in, or near, the estuary of the natal river. To our knowledge, this is the first published report on in situ measurements of salinity levels experienced by free-ranging brown trout in a marine habitat but see 40 . Based on previous studies, it has been shown that brown trout are variable in their use of estuaries.…”
Section: Discussionmentioning
confidence: 99%
“…The spacing between the needles matched the length of the tag. To avoid erosion of the flesh by the tag or attachment wire, a silicone plate was attached between the tag and the skin, and a plastic plate was attached between the skin and the wire on the opposing dorsal side 40 . Throughout the tagging process, the gills were irrigated with fresh, ambient river water.…”
Section: Methodsmentioning
confidence: 99%